In-situ mullite whisker toughened silicon-based ceramic core and preparation method thereof
By generating mullite whiskers in situ within a silicon-based ceramic core, the problems of brittleness and high-temperature deformation in silicon-based ceramic cores are solved, achieving high-performance and low-cost toughening effects, suitable for the manufacture of turbine blades for aero-engines and gas turbines.
Patent Information
- Application Number
- CN202511676677.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2025-12-12
- Estimated Expiration
- 2045-11-14
AI Technical Summary
Existing technologies cannot effectively solve the problems of poor thermal shock resistance, insufficient high-temperature strength, and easy deformation and fracture caused by the brittleness of silicon-based ceramic cores. In particular, in the manufacturing of turbine blades for aero-engines, existing methods are costly, complex, and have limited toughening effects.
By generating mullite whiskers in situ in a silicon-based ceramic core, using mica scraps as a low-cost precursor, and combining the gas-phase transport effect of fluoride mineralizers, a mullite whisker reinforcing phase is constructed during high-temperature sintering, which improves the fracture behavior and interfacial bonding of the material. A secondary shaping process using slurry dipping is adopted to ensure shape stability.
It significantly improves the room temperature and high temperature flexural strength of ceramic cores, suppresses high temperature viscous flow, ensures the molding capability and dimensional accuracy of complex structures, reduces production costs and process complexity, and is suitable for aero engines and high-performance gas turbines.
Smart Images

Figure CN121104023A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of ceramic core preparation, and particularly relates to a silicon-based ceramic core toughened by in-situ mullite whiskers and a preparation method thereof. BACKGROUND
[0002] Hollow turbine blades, as key hot-end components of aero-engines and gas turbines, have complex internal cooling channel structures formed by silica-based ceramic cores in precision casting. Therefore, the ceramic cores must have extremely high dimensional accuracy and shape stability. However, the silica-based ceramic cores are subject to severe challenges in the directional solidification process due to their inherent brittleness and low thermal shock resistance. When subjected to the surrounding and erosion of high-temperature molten alloy for a long time, the cores are prone to softening and forming a low-viscosity glass phase, resulting in high-temperature deformation and directly affecting the forming accuracy of the blades. In a harsh service environment, the inner cavity of the core is prone to grain coarsening or harmful phase transformation due to high temperature, high pressure and high-speed rotating stress, and in severe cases, the ceramic core may even break, thereby greatly shortening its service life.
[0003] To improve the high-temperature mechanical properties of silica-based ceramic cores, in-situ growth of whisker strengthening phases in the ceramic matrix is considered as an effective means. This method can achieve significant toughening and reinforcing effects by adjusting the number and morphology of the whiskers, optimizing the microstructure and enhancing the interfacial bonding strength between the whiskers and the matrix. However, the existing technologies that introduce mullite whiskers (such as the molten salt method and the fluoride catalyst method) generally have the following bottlenecks: (1) high raw material cost: it is heavily dependent on high-purity alumina, silica or complex pretreated fly ash as precursors, and the molten salt method also faces environmental and cost pressures in waste salt treatment; (2) poor interface bonding and dispersibility: exogenously added pre-synthesized whiskers are difficult to disperse uniformly in the matrix, and are prone to become stress concentration points due to agglomeration, and there are often pores or weak bonding at the interface between the whiskers and the matrix, which limits the toughening effect; (3) complex process and high energy consumption: traditional methods usually require ultra-high sintering temperatures above 1600℃, and involve multiple processes such as whisker pre-synthesis and dispersion mixing, resulting in a prolonged production cycle and an increased energy consumption of 20%-30% compared to conventional processes, which is less economical.
[0004] The existing patent CN106747541A discloses a preparation method of mullite ceramic with in-situ synthesized mullite whiskers for self-toughening. However, this technology is mainly aimed at dense structural ceramic products, and there are essential differences in material system, sintering system and performance targets between the porous, soluble and silica-based ceramic cores. Therefore, this scheme cannot be directly applied to the preparation of ceramic cores, and still relies on high-purity alumina and silica as raw materials, and needs to add expensive mullite seeds, which does not fundamentally solve the problem of high cost.
[0005] The existing patent CN112047726A proposes a mullite whisker reinforced aluminum-based ceramic core. The core of this technology is to use fused alumina as the base of the "aluminum-based" core system, which has essential differences in application scenarios and performance requirements from the "silicon-based" core. Its technical means are all around the design of the aluminum-based system, and it does not touch the core problems of the brittle silica-based ceramic core material and the easy deformation at high temperature. In addition, the raw material cost of this technology is higher, and the process complexity has not been reduced.
[0006] In summary, the above-mentioned existing patents have not provided an effective toughening scheme for "silicon-based" ceramic cores with low cost, high performance and excellent processability. Therefore, developing an innovative preparation method that can fundamentally improve the brittleness of silicon-based ceramic cores, improve their thermal shock resistance and high temperature stability, to meet the harsh demands of aero-engine on high-performance turbine blades, has become a technical problem to be solved in the field. SUMMARY
[0007] Based on the current status of the prior art, the present application proposes a mullite whisker toughened silicon-based ceramic core and a preparation method thereof, which solves the problems of poor thermal shock resistance, insufficient high temperature strength and easy deformation and fracture of silicon-based ceramic cores caused by intrinsic brittleness in the prior art.
[0008] To achieve the above-mentioned purpose, in one aspect of the radical application, a preparation method of a mullite whisker toughened silicon-based ceramic core is proposed. The specific technical scheme is as follows: A preparation method of a mullite whisker toughened silicon-based ceramic core, the preparation method comprising the following steps: S1, wet ball milling mica plate offcut to obtain uniform powder, soaking the powder in ammonia water to remove surface sizing agent, and then performing solid-liquid separation to obtain pure mica powder; S2, mixing the fused quartz glass powder, mica powder and mineralizer in proportion, then adding the plasticizer and mixing uniformly to obtain a ceramic core slurry; S3, hot press injection molding the ceramic core slurry to obtain a ceramic core green body; S4, dipping the ceramic core green body in the ceramic core slurry of step S2 for secondary shaping; S5, burying the secondary shaped ceramic core green body in alumina powder, and performing multi-stage temperature control high temperature sintering to generate mullite whiskers in situ, to obtain a ceramic core sintered body; S6, immersing the ceramic core sintered body in a composite strengthening liquid, taking it out after soaking and drying to obtain a ceramic core; S7, removing the excess part of the dried ceramic core.
[0009] Further, in step S2, the content of each component is: fused quartz glass powder: 55-80 wt.%; mica powder: 5-15 wt.%; mineralizer: 1-10 wt.%; plasticizer: 10-20 wt.% based on 100% of the total mass of the ceramic core slurry.
[0010] Further, in step S2, the content of each component is: fused quartz glass powder: 65-75 wt.%; mica powder: 9-12 wt.%; mineralizer: 6-8 wt.%; plasticizer: 10-15 wt.% based on 100% of the total mass of the ceramic core slurry.
[0011] Further, the plasticizer includes at least one of semi-refined paraffin wax, polyethylene, ozokerite and bleached wax; and the mineralizer includes ice and / or aluminum trifluoride.
[0012] Further, in step S1, the mica plate offcut of different particle sizes is collected, cleaned, washed, then wet ball milled, dried, sieved to obtain the mica powder; the mica powder is soaked in a heated ammonia water solution, then subjected to solid-liquid separation, and the mica powder is dried for standby use.
[0013] Further, in step S1, the ball-to-material ratio of the wet ball milling is (1-2):1, the ball milling time is 6-12 h, and the ball milling rotation speed is 150-300 r / min. The concentration of the ammonia water solution is 1-15 mol / L, and the soaking treatment time is 30-60 min. The drying temperature of the mica powder is 95-120℃, and the drying time is 12-24 h.
[0014] Further, in step S3, the pressing temperature of the hot press injection molding is 70-85℃, the injection flow rate is 300-320 cc / sec, and the molding pressure is 5-10 MPa.
[0015] Further, in step S6, the composite reinforcing liquid is composed of the following components in percentage by mass: ethyl silicate 63.6%, silica sol 20.2%, styrene-butadiene rubber 15.8%, fatty alcohol polyoxyethylene ether 0.4%, and solvent 2.0%; the soaking is carried out at 60-85℃, and the soaking time is 30-60 min.
[0016] Further, in step S5, the multi-stage temperature control high-temperature sintering includes four temperature rising stages, wherein the first stage is to rise from room temperature to 200-300℃ at a rate of 2-3℃ / min and keep for 6-8h; the second stage is to rise to 500-600℃ at a rate of 3-5℃ / min and keep for 2-4h; the third stage is to rise to 800-900℃ at a rate of 2-3℃ / min and keep for 4-6h; and the fourth stage is to rise to the highest sintering temperature of 1200-1300℃ at a rate of 0.5-1℃ / min and keep for 6-8h.
[0017] Another aspect of the present application is to provide a silicon-based ceramic core toughened by in-situ mullite whiskers. The silicon-based ceramic core toughened by in-situ mullite whiskers comprises 55-80wt.% of fused quartz glass powder, 5-15wt.% of mica powder, 1-10wt.% of mineralizer and 10-20wt.% of plasticizer; and the quartz glass matrix of the ceramic core is distributed with in-situ self-grown mullite whiskers.
[0018] Compared with the prior art, the present application has at least the following beneficial effects: 1. The silicon-based ceramic core toughened by in-situ mullite whiskers and the preparation method thereof change the fracture behavior of the material by in-situ generating mullite whiskers in the matrix, thereby significantly improving the room temperature and high temperature bending strength of the ceramic core and endowing it with excellent high temperature creep resistance, and ensuring the structural integrity of the core in the directional solidification process.
[0019] 2. The in-situ grown whiskers play a "skeleton" supporting role in the sintering process, effectively inhibiting the viscous flow and shrinkage of the quartz matrix at high temperature, and the combined "dipping secondary sizing" process together ensures the shape stability of the green body and the sintered body. This scheme makes the sintering shrinkage rate of the ceramic core stable and controlled at a low level, providing reliable guarantee for manufacturing hollow turbine blades with complex internal cavities and extremely high requirements for size precision.
[0020] 3. Although the reinforcing phase is introduced, the mica, mineralizer and the like used in the present application are all micron-sized powders, which have good particle size matching with the quartz powder matrix. This makes the prepared ceramic slurry still maintain excellent rheological properties and filling capacity, and is completely suitable for hot press injection molding of ceramic cores with complex structures, ensuring the feasibility of the production process.
[0021] 4. This invention proposes an in-situ mullite whisker-toughened silicon-based ceramic core and its preparation method. It creatively replaces the high-purity alumina and silicon dioxide used in traditional methods with mica plate scraps, achieving waste utilization and avoiding the dispersion and interfacial bonding problems caused by added whiskers. This solution fundamentally solves the bottlenecks of high raw material costs and complex processes in the background technology, providing a solution that combines high performance and excellent economy. It is not only suitable for aero-engine turbine blades but also has broad prospects for application in fields such as high-performance gas turbines. Attached Figure Description
[0022] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 A schematic flowchart of the preparation method of an in-situ mullite whisker-toughened silicon-based ceramic core proposed in this invention is shown. Figure 2 A scanning electron microscope (SEM) schematic diagram of the ceramic core sintered body prepared in Example 2 of the present invention is shown; Figure 3 Showed with Figure 2 EDS element surface distribution map of the corresponding region. Detailed Implementation
[0023] The present invention will be further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other.
[0024] To address the problems of poor thermal shock resistance, insufficient high-temperature strength, and easy deformation and fracture caused by the intrinsic brittleness of existing silicon-based ceramic cores, this invention proposes an in-situ mullite whisker-reinforced silicon-based ceramic core and its preparation method. This method forms a mullite whisker reinforcing phase in the matrix through an in-situ reaction, which significantly improves the high-temperature flexural strength and high-temperature creep resistance of the ceramic core. The prepared silicon-based ceramic core features uniform mullite whisker distribution, low surface roughness, and high dimensional accuracy. It exhibits excellent deformation resistance at high temperatures and is suitable for the directional solidification precision casting of turbine blades for next-generation aero-engines and high-performance gas turbines, potentially significantly improving the manufacturing precision and yield of hollow blades.
[0025] To achieve the above objectives, according to one aspect of the present invention, a method for preparing an in-situ mullite whisker-toughened silicon-based ceramic core is provided, see reference. Figure 1 As shown, the specific steps include: S1 clean up the different size mica plate scraps, rinse and wet ball mill to uniform, dry, sieve to get mica powder, soak in heated ammonia water to remove surface glue, dry in air after solid-liquid separation for standby; S2, melt quartz glass powder, mica powder and mineralizer in a mixer to mix well, then dry in a vacuum dryer, add the dry mixed powder into the melted plasticizer, stir well under vacuum to get ceramic core slurry; S3, inject the ceramic core slurry into the mold for hot press injection molding to prepare ceramic core green body; S4, dip the shaped ceramic core green body into the ceramic core slurry of step S2 to form a slurry coating on the surface, which can effectively enhance the surface strength of the green body and provide support during the initial sintering, thereby achieving secondary shaping and preventing deformation; S5, embed the ceramic core green body in light alumina and sinter at high temperature to obtain a ceramic core; S6, immerse the sintered ceramic core in a composite strengthening liquid in a vacuum environment, dry naturally after soaking, and obtain a finished ceramic core; S7, remove the excess part of the finished ceramic core by mechanical processing or grinding.
[0026] In step S1, the ball-to-material ratio of wet ball milling is (1-2):1, the ball milling time is 6-12h, and the ball milling speed is 150-300r / min; the particle size of the mica powder obtained after sieving is 50-100μm; the soaking time in ammonia water is 30-60min, and the concentration of ammonia water is 1-15mol / L; the drying temperature of the mica powder is 95-120℃, and the drying time is 12-24h; The mica powder includes about 45-50 wt% SiO2 and about 30-38 wt% Al2O3, 6-10 wt% K2O, and 0.5-4 wt% other impurity oxides.
[0027] In step S2, the mass percentage of the fused quartz glass powder in the ceramic core slurry is 55-80wt.%, the mass percentage of the mica powder in the ceramic core slurry is 5-15wt.%, the weight percentage of the mineralizer in the ceramic core slurry is 1-10wt.%, and the weight percentage of the plasticizer in the ceramic core slurry is 10-20wt.%; the temperature of the plasticizer is 60-90℃, and the stirring time in the plasticizer is 3-4h.
[0028] The plasticizer includes one or more of semi-refined paraffin wax, polyethylene, ozokerite, and bleached wax, and the mineralizer includes one or both of ice crystal and aluminum trifluoride.
[0029] The particle size of the fused quartz glass powder is 1-50 μm, and the purity is ≥99%; the particle size of the mineralizer is 1-50 μm, and the purity is ≥99%.
[0030] In step S3, the pressing temperature in the hot-press injection molding process is 70-85℃, the injection flow is 300-320 cc / sec, and the molding pressure is 5-10 Mpa.
[0031] In step S5, the particle size of the light-weight alumina powder is 1-50 μm, and the purity is ≥99.95%; the high-temperature sintering includes four stages, from room temperature to 1200-1300℃, specifically: the first stage is from room temperature to 200-300℃, the heating rate is 2-3℃ / min, and the holding time is 6-8h; the second stage is from 200-300℃ to 500-600℃, the heating rate is 3-5℃ / min, and the holding time is 2-4h; the third stage is from 500-600℃ to 800-900℃, the heating rate is 2-3℃ / min, and the holding time is 4-6h; the fourth stage is from 800-900℃ to the highest sintering temperature, the heating rate is 0.5-1℃ / min, and the holding time is 6-8h at the highest sintering temperature.
[0032] In step S6, the composite strengthening liquid is composed of the following components: ethyl silicate 63.6%, silica sol 20.2%, butadiene styrene rubber 15.8%, and fatty alcohol polyoxyethylene ether 0.4%; the temperature of the composite strengthening liquid is 60-85℃, and the soaking time is 30-60 min. Since the ceramic core has a porosity of about 20-30% after sintering, the composite strengthening liquid needs to penetrate into the core through these internal pores. In a vacuum environment, not only is it beneficial to speed up the penetration speed, but it can also effectively remove the bubbles in the strengthening liquid, thereby improving the strengthening effect.
[0033] The application provides a preparation method of a silicon-based ceramic core toughened by in-situ mullite whiskers, and the core principle is as follows: mica plate offcut is used as a low-cost precursor, and a fluoride mineralizer is used to realize in-situ construction of mullite whisker reinforcing phase in the silicon-based ceramic during high-temperature sintering, so that the silicon-based ceramic core is significantly toughened. The process starts after the sintering temperature is increased, and the added mineralizer (such as AlF3) is first sublimated to generate aluminum trifluoride (AlF3), aluminum oxyfluoride (AlOF) and other gas phase components. These gas phase substances penetrate into the interface between mica powder and molten quartz (SiO2), which activates the quartz glass phase on one hand and promotes the thermal decomposition of the mica raw material on the other hand, and generates high-activity reaction intermediates. Then, through the efficient gas-solid phase mass transfer process, the aluminum and silicon components in the system are continuously transported to provide necessary conditions for the nucleation and growth of mullite (3Al2O3·2SiO2). In the anisotropic gas phase growth environment, the mullite nucleus tends to grow preferentially and rapidly along the c-axis direction, and finally develops into needle-shaped or whisker-shaped crystals with a high aspect ratio. The in-situ grown mullite whiskers are chemically combined with the quartz glass matrix to effectively dissipate the fracture energy, so that the ceramic core is significantly endowed with higher room temperature and high-temperature bending strength, excellent high-temperature creep resistance and dimensional stability. At the same time, since the mica offcut and the mineralizer used are micron-sized powders, they have good particle size matching and mixing uniformity with the quartz powder, and do not damage the rheological properties and injection molding capability of the quartz-based ceramic slurry, so that the green body of the complex structure ceramic core can be successfully formed.
[0034] The preparation method of the ceramic core with oriented whisker reinforcement according to the application is described below in combination with specific data values.
[0035] Example 1 S1, after the collected mica plate offcut is ground and crushed, the mica plate offcut is washed and soaked in deionized water for a period of time to remove surface impurities, and the treated mica plate offcut is added into a ball mill tank according to a ball-to-material ratio of 1.5:1 for wet ball milling at a speed of 200 r / min for 10 h, and then the mica plate offcut is dried and sieved to obtain a uniform powder; ammonia water with a concentration of 5 mol / L is added to the powder and soaked at 95℃ for 60 min, and then solid-liquid separation is performed to obtain pure mica powder, which is dried at 95℃ in air for 24 h for standby; S2, the semi-refined paraffin wax, polyethylene, ozocerite, bleached wax are placed in a wax kettle according to the mass ratio of 8:1:1:1, heated to 90℃ and stirred for 3h to melt and form a plasticizer. The ceramic core slurry is prepared according to the weight percentage: 65.0% of fused quartz glass powder, 12.0% of mica powder, 8.0% of mineralizer (ice and aluminum trifluoride) and 15% of plasticizer; the fused quartz glass powder, mica powder and mineralizer are added to a mixer and stirred thoroughly, then placed in a vacuum dryer to dry, and the dried mixed powder batch is added to the plasticizer at 65℃, vacuum stirring for 3h to obtain the ceramic core slurry; S3, the ceramic core slurry is transferred to the core pressing machine barrel, and the ceramic core slurry is hot-pressed and injected into the ceramic core mold, the pressing temperature of the core pressing machine is 70℃, the injection pressure is 5Mpa, and the injection flow rate is 300cc / sec, to obtain the ceramic core preform green body; S4, the shaped ceramic core is quickly dipped in the ceramic core slurry in step S2 for secondary shaping and natural drying; S5, the secondary shaped ceramic core preform green body is embedded in a sagger filled with light weight alumina powder for sintering, from room temperature to 250℃ at a rate of 2℃ / min, holding for 7h; then to 550℃ at a rate of 3℃ / min, holding for 3h; then to 850℃ at a rate of 3℃ / min, holding for 5h; finally to the final sintering temperature of 1250℃ at a rate of 0.5℃ / min, and holding for 7h, and then naturally cooling to room temperature in the furnace to obtain the ceramic core sintered body; S6, under vacuum, the sintered ceramic core is immersed in a preheated composite strengthening liquid at 60℃, and then soaked at 60℃ for 30 minutes for strengthening treatment, and then taken out and naturally dried to obtain the finished ceramic core; S7, the flash and runner of the sintered ceramic core are removed using a polishing needle and a brush.
[0036] The ceramic core is detected by CT scanning, and the shrinkage rate is calculated by the measured size of the ceramic core green body before and after sintering. The ceramic core of this embodiment is measured and calculated, and the room temperature bending strength is 30.57MPa, the bending strength at 1550℃ is 40.57MPa, the deflection at 1550℃ is 0.08mm, the porosity is 30.5%, and the shrinkage rate is 1.42%.
[0037] Example 2 S1, the collected mica plate edge material is ground and crushed, then washed with deionized water and soaked for a period of time to remove surface impurities, the treated mica plate edge material is added to a ball mill tank at a ball to material ratio of 2:1 for wet ball milling at a speed of 250 r / min for 8 h, then dried, sieved to obtain a uniform powder; 10 mol / L ammonia water is added to the powder and soaked at 95°C for 50 min, then solid-liquid separation is performed to obtain pure mica powder, which is dried at 100°C in air for 20 h for standby; S2, the semi-refined paraffin wax, polyethylene and ozokerite are placed in a wax kettle according to a mass ratio of 10:2:1 and heated to 90°C for stirring for 3 h to melt and form a plasticizer. The ceramic core slurry is prepared according to the following weight percentage: 75.0% of fused quartz glass powder, 9.0% of mica powder, 6.0% of mineralizer (ice and aluminum trifluoride), and 10% of plasticizer; the fused quartz glass powder, mica powder and mineralizer are added to a mixer and stirred thoroughly, then placed in a vacuum drying machine for drying, and the dried mixed powder is added to the plasticizer at 75°C, vacuum stirring for 4 h to obtain the ceramic core slurry; S3, the ceramic core slurry is transferred to the core pressing machine barrel, and the ceramic core slurry is hot-pressed and injected into the ceramic core mold, the pressing temperature of the core pressing machine is 80°C, the injection pressure is 10 MPa, and the injection flow rate is 300 cc / sec, to obtain a ceramic core preform green body; S4, the shaped ceramic core is quickly dipped in the ceramic core slurry of step S2 for secondary shaping and natural drying; S5, the secondary shaped ceramic core preform green body is embedded in a sagger filled with light weight alumina powder for sintering, from room temperature to 300°C at a rate of 2°C / min, holding for 6 h; then from 300°C to 600°C at a rate of 3°C / min, holding for 3 h; then from 600°C to 900°C at a rate of 3°C / min, holding for 4 h; finally from 900°C to the final sintering temperature of 1300°C at a rate of 0.5°C / min, holding for 6 h, and then naturally cooling to room temperature in the furnace to obtain a ceramic core sintered body; S6, the sintered ceramic core is immersed in a preheated composite strengthening liquid at 70°C under vacuum, and soaked at 70°C for 30 min for strengthening treatment, then taken out and naturally dried, to obtain a finished ceramic core; S7, the flash and runner of the sintered ceramic core are removed using a polishing needle and a brush.
[0038] The ceramic core is detected by CT scanning, and the shrinkage is calculated by the green body size of the ceramic core and the size of the ceramic core measured before and after sintering. The ceramic core of the embodiment is measured and calculated, and the room temperature bending strength is 34.57 MPa, the bending strength at 1550℃ is 43.57 MPa, the deflection at 1550℃ is 0.02 mm, the porosity is 31.5%, and the shrinkage is 1.38%.
[0039] Referring to Figure 2 The scanning electron microscope (SEM) photo of the sintered body of the ceramic core prepared in the embodiment is shown in FIG. 2, from which it can be observed that needle-shaped or whisker-shaped mullite crystals are generated in situ in the quartz glass matrix (the coil in the figure encloses the whisker-shaped crystals).
[0040] Referring to Figure 3 The EDS element area analysis chart of the corresponding area of the SEM chart is shown in FIG. 3, and the analysis result shows that the distribution position of the aluminum element is highly coincident with the whisker-shaped crystal morphology observed in the SEM photo, referring to Figure 3 (a) shown; at the same time, the area is also rich in silicon element and oxygen element, referring to Figure 3 (b) and Figure 3 (c) shown; this proves from the spatial distribution of elements that the whisker-shaped crystal is composed of aluminum, silicon and oxygen. Through the formula and process provided by the present application, mullite whiskers are successfully synthesized in situ from the mica plate offcuts. The reinforcing structure can effectively hinder crack propagation and withstand high temperature load, which directly explains why the embodiment has the highest high temperature strength and excellent creep resistance.
[0041] Example 3 S1, after the collected mica plate offcuts are ground and crushed, they are washed with deionized water and soaked for a period of time to remove surface impurities, and the treated mica plate offcuts are added to a ball mill tank at a ball-to-material ratio of 1.4:1 for wet ball milling at a speed of 300 r / min for 12 h, and then dried, sieved and uniformly powdered; ammonia water with a concentration of 15 mol / L is added to the powder and soaked at 95℃ for 45 min, and then solid-liquid separation is performed to obtain pure mica powder, which is dried at 115℃ in air for 18 h for standby; S2, the semi-refined paraffin wax, the ozocerite and the bleached wax are placed in a wax kettle according to a mass ratio of 12:2:1, heated to 90℃ and stirred for 3 h to melt and form a plasticizer. The ceramic core slurry is prepared according to the weight percentage: 55.0% of fused quartz glass powder, 15.0% of mica powder, 10.0% of mineralizer aluminum trifluoride and 20% of plasticizer; the fused quartz glass powder, mica powder and mineralizer are added to a mixer and stirred thoroughly, and then placed in a vacuum drying machine for drying; the dried mixed powder is added to the plasticizer at 80℃, and vacuum stirring is performed for 3.5 h to obtain the ceramic core slurry; S3, transfer the ceramic core slurry to the core pressing machine barrel, and hot-press injection of the ceramic core slurry into the ceramic core mold, the pressing temperature of the core pressing machine is 75℃, the injection pressure is 8.5Mpa, and the injection flow is 310cc / sec, to obtain a ceramic core preform green body; S4, the shaped ceramic core is quickly dipped in the ceramic core slurry in step S2 for secondary shaping and natural drying; S5, the secondary shaped ceramic core preform green body is embedded in a sagger filled with light weight alumina powder for sintering, from room temperature to 300℃ at a rate of 3℃ / min, holding for 6h; then to 600℃ at a rate of 3℃ / min, holding for 2h; then to 900℃ at a rate of 3℃ / min, holding for 6h; finally to the final sintering temperature of 1200℃ at a rate of 0.5℃ / min, holding for 8h, and naturally cooling to room temperature in the furnace to obtain a ceramic core sintered body; S6, under vacuum, the sintered ceramic core is immersed in a preheated composite strengthening liquid at 75℃, and soaked at 75℃ for 30min for strengthening treatment, then taken out and naturally dried, to obtain a finished ceramic core; S7, using a polishing needle and a brush to remove the excess part of the sintered ceramic core such as flash and runner.
[0042] The ceramic core is detected by CT scanning, and the shrinkage rate is calculated by the measured size of the ceramic core green body before and after sintering. The ceramic core of this embodiment is measured and calculated, and the room temperature bending strength is 35.57MPa, the bending strength at 1550℃ is 40.1MPa, the deflection at 1550℃ is 0.32mm, the porosity is 26.8%, and the shrinkage rate is 1.12%.
[0043] Example 4 S1, after the collected mica plate scraps are ground and crushed, they are washed with deionized water and soaked for a period of time to remove surface impurities, and the treated mica plate scraps are added to a ball mill tank at a ball to material ratio of 1.8:1 for wet ball milling at a speed of 225r / min for 9h, and then dried and sieved to obtain a uniform powder; ammonia water with a concentration of 8mol / L is added to the powder and soaked at 95℃ for 45min, then solid-liquid separation is performed to obtain pure mica powder, which is placed in air and dried at 120℃ for 20h for standby; S2, the semi-refined paraffin wax and bleached wax are placed in a wax kettle in a mass ratio of 8:1 and heated to 90℃ and stirred for 3h to melt and form a plasticizer. The ceramic core slurry is prepared according to the weight percentage: 80.0% of fused quartz glass powder, 5.0% of mica powder, 1.0% of mineralizer aluminum trifluoride, and 14% of plasticizer; the fused quartz glass powder, mica powder, and mineralizer are added to a mixer and stirred thoroughly, then placed in a vacuum dryer to dry, and the dried mixed powder batch is added to the plasticizer at 90℃, vacuum stirring for 3h to obtain the ceramic core slurry; S3, the ceramic core slurry is transferred to the core pressing machine barrel, and the ceramic core slurry is hot-pressed and injected into the ceramic core mold, the pressing temperature of the core pressing machine is 85℃, the injection pressure is 7.5Mpa, and the injection flow rate is 320cc / sec, to obtain the ceramic core preform green body; S4, the shaped ceramic core is quickly dipped in the ceramic core slurry of step S2 for secondary shaping and natural drying; S5, the secondary shaped ceramic core preform green body is embedded in a sagger filled with light weight alumina powder for sintering, from room temperature to 200℃ at a rate of 2℃ / min, holding for 8h; then to 600℃ at a rate of 3℃ / min, holding for 3h; then to 900℃ at a rate of 3℃ / min, holding for 6h; finally to the final sintering temperature of 1250℃ at a rate of 1℃ / min, and holding for 7h, and then naturally cooling to room temperature in the furnace to obtain the ceramic core sintered body; S6, under vacuum, the sintered ceramic core is immersed in a preheated composite strengthening liquid at 75℃, and soaked at 75℃ for 30 minutes for strengthening treatment, then taken out and naturally dried, and finally the finished ceramic core is obtained; S7, the flash and runner of the sintered ceramic core are removed using a polishing needle and a brush.
[0044] The ceramic core is detected by CT scanning, and the shrinkage rate is calculated using the measured dimensions of the ceramic core green body before and after sintering. The ceramic core of this embodiment has a room temperature bending strength of 22.51MPa, a bending strength at 1550℃ of 28.1MPa, a deflection at 1550℃ of 0.42mm, a porosity of 34.8%, and a shrinkage rate of 1.64%.
[0045] Comparative Example S1, put semi-refined paraffin wax 0.4 kg, polyethylene 0.05 kg, ozocerite 0.05 kg, bleached wax 0.05 kg into a wax kettle and heat to 90℃ for 2h with stirring to form a plasticizer; put 8.5 kg of fused quartz glass powder, 0.3 kg of ice crystal and 0.3 kg of aluminum trifluoride into a mixer and stir for 2h, then put them into a vacuum drying machine and dry for 12h at a drying temperature of 110℃, then add the dried mixed powder into the molten plasticizer in batches, vacuum stir for 1h to uniform, and obtain a ceramic core slurry; S2, transfer the above ceramic core slurry to the core pressing machine barrel, and hot-press inject the ceramic core raw material into the ceramic core mold, the pressing temperature of the core pressing machine during pressing is 65℃, the injection pressure is 5Mpa, and the injection flow rate is 300cc / sec, to obtain a green body of ceramic core; S3, dip the shaped green body of ceramic core into the above ceramic core slurry for secondary shaping, and naturally cool; S4, embed the secondary shaped green body of ceramic core in a sagger filled with light weight alumina powder for sintering, from room temperature to 200℃ at a rate of 2℃ / min, and keep the temperature for 6h; then increase the temperature to 600℃ at a rate of 3℃ / min, and keep the temperature for 4h; then increase the temperature to 800℃ at a rate of 3℃ / min, and keep the temperature for 6h; finally increase the temperature to the final sintering temperature of 1180℃ at a rate of 2℃ / min, and keep the temperature for 6h, and then naturally cool to room temperature in the furnace to obtain a sintered body of ceramic core; S5, immerse the sintered ceramic core into ethyl silicate composite strengthening liquid for 30min for strengthening treatment under vacuum environment, then take it out and naturally dry to obtain the final ceramic core product; S6, use a polishing needle and a brush to remove the excess ceramic core after sintering.
[0046] The shrinkage rate is calculated by measuring the size of the ceramic core green body before and after sintering. The ceramic core of this embodiment has a room temperature bending strength of 7.35MPa, a bending strength at 1550℃ of 15.35MPa, a deflection at 1550℃ of 0.56mm, a porosity of 36.5%, and a shrinkage rate of 1.58%.
[0047] In order to achieve the above object, according to another aspect of the present application, there is provided a silicon-based ceramic core toughened by in-situ mullite whiskers, raw materials of the silicon-based ceramic core including fused quartz glass powder, mica powder, mineralizer and plasticizer, wherein the fused quartz glass powder is 55-80wt.%, the mica powder is 5-15wt.%, the mineralizer is 1-10wt.%, and the plasticizer is 10-20wt.%. The microstructure of the silicon-based ceramic core is characterized in that mullite whiskers are distributed in the quartz glass matrix, and the mullite whiskers effectively transfer the load by whisker bridging, crack deflection and pull-out effect, hinder crack propagation, thereby significantly improving the room temperature and high temperature strength, thermal shock resistance and dimensional stability of the core.
[0048] The preferred embodiments of the present application have been described above with the preferred embodiments, but the present application is not limited to them and can be variously changed and modified by those skilled in the art. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the present application.
[0049] It should be noted that the terms "comprising", "including", or any other variant thereof are intended to cover non-exclusive inclusions, so that processes, methods, articles or devices including a series of elements not only include those elements, but also include other elements not explicitly listed or inherent to such processes, methods, articles or devices. Without more limitations, the element defined by the phrase "including a" does not exclude the presence of another identical element in the process, method, article or device including the element.
[0050] It should be noted that in the description of the present specification, the description referring to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any appropriate manner in any one or more embodiments or examples. Furthermore, the person skilled in the art can combine and combine the different embodiments or examples described in the present specification and the features of the different embodiments or examples, without contradiction.
Claims
1. A method for preparing an in-situ mullite whisker-reinforced silicon-based ceramic core, characterized in that, The preparation method includes the following steps: S1. The mica board scraps are wet ball milled to obtain uniform powder. The powder is soaked in ammonia water to remove the surface adhesive, and then solid-liquid separation is performed to obtain pure mica powder. S2. Mix fused silica glass powder, mica powder, and mineralizer in a certain proportion until uniform, then add plasticizer and mix until uniform to obtain ceramic core slurry; S3. The ceramic core slurry is hot-pressed and injected to obtain a ceramic core blank; S4. Quickly dip the ceramic core blank into the ceramic core slurry described in step S2 for secondary shaping. S5. The ceramic core blank, which has undergone secondary shaping, is embedded in alumina powder and sintered at high temperature under controlled temperature in multiple stages to generate mullite whiskers in situ, thus obtaining the sintered ceramic core. S6. Immerse the ceramic core sintered body in the composite strengthening liquid, and after soaking, take it out and dry it to obtain the ceramic core. S7. Remove any excess material from the dried ceramic core.
2. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 1, characterized in that, In step S2, based on the total mass of the ceramic core slurry as 100%, the content of each component is as follows: fused silica glass powder: 55-80 wt.%; mica powder: 5-15 wt.%; mineralizer: 1-10 wt.%; Plasticizer: 10-20 wt.%.
3. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 2, characterized in that: In step S2, based on the total mass of the ceramic core slurry as 100%, the content of each component is as follows: fused silica glass powder: 65-75 wt.%; mica powder: 8-12 wt.%; mineralizer: 5-8 wt.%; Plasticizer: 10-15 wt.%.
4. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 1, characterized in that: The plasticizer includes at least one of semi-refined paraffin wax, polyethylene, ceresin wax, and bleaching wax; the mineralizer includes cryolite and / or aluminum trifluoride.
5. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 1, characterized in that: In step S1, mica board scraps of different particle sizes are collected, cleaned, rinsed, and then wet-milled. After drying and sieving, mica powder is obtained. The mica powder is soaked in a heated ammonia solution, followed by solid-liquid separation. The mica powder is then dried and ready for use.
6. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 5, characterized in that: In step S1, the ball-to-material ratio of the wet ball mill is (1-2):1, the ball milling time is 6-12h, and the ball milling speed is 150-300r / min; The concentration of the ammonia solution is 1-15 mol / L, and the soaking time is 30-60 min; The mica powder is dried at a temperature of 95-120℃ for 12-24 hours.
7. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 1, characterized in that, In step S3, the pressing temperature of the hot-press injection molding is 70-85℃, the injection flow rate is 300-320cc / sec, and the molding pressure is 5-10Mpa.
8. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 1, characterized in that... In step S6, the composite reinforcing liquid is composed of the following components by mass percentage: 63.6% ethyl silicate, 20.2% silica sol, 15.8% styrene-butadiene rubber, 0.4% fatty alcohol polyoxyethylene ether, and 2.0% solvent; the soaking is carried out at 60-85°C for 30-60 min.
9. The method for preparing the in-situ mullite whisker-toughened silicon-based ceramic core according to claim 1, characterized in that: In step S5, the multi-stage temperature-controlled high-temperature sintering includes four heating stages: the first stage heats the temperature from room temperature to 200-300℃ at a rate of 2-3℃ / min and holds it for 6-8 hours; the second stage heats the temperature to 500-600℃ at a rate of 3-5℃ / min and holds it for 2-4 hours; the third stage heats the temperature to 800-900℃ at a rate of 2-3℃ / min and holds it for 4-6 hours; and the fourth stage heats the temperature to the maximum sintering temperature of 1200-1300℃ at a rate of 0.5-1℃ / min and holds it for 6-8 hours.
10. A silicon-based ceramic core toughened with in-situ mullite whiskers, characterized in that: The raw materials of the ceramic core include 55-80 wt.% fused silica glass powder, 5-15 wt.% mica powder, 1-10 wt.% mineralizer and 10-20 wt.% plasticizer; the quartz glass matrix of the ceramic core contains in-situ self-generated mullite whiskers.
Citation Information
Patent Citations
Method for in-situ synthesizing mullite whisker self-toughened mullite ceramics
CN106747541A
Preparation method of mica / TiO2 / Al2O3 / Co2O3 seven-layer structure angle-dependent different-color paint
CN101565565A
Low dielectric resin composition, prepreg and film, copper foil laminated plate and printed circuit board
CN102702481A
High-toughness and high-shock-resistance polyvinyl chloride cable material and preparation method thereof
CN103467881A
Preparation method of in-situ self-generating mullite whisker reinforced silicon-based ceramic core
CN112062587A